2006
DOI: 10.1183/09031936.06.00037005
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of abnormal acid gastro-oesophageal reflux in idiopathic pulmonary fibrosis

Abstract: The aim of this prospective study was to determine the prevalence and characteristics of acid gastro-oesophageal reflux (GER) in patients with idiopathic pulmonary fibrosis (IPF).Sixty-five consecutive patients with well-defined IPF were subjected to 24-h pH monitoring and oesophageal manometry. A total of 133 consecutive patients with intractable asthma and symptoms of GER were used as comparisons.The prevalence of abnormal acid GER in IPF patients was 87%, with 76% and 63% demonstrating abnormal distal and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
411
4
32

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(463 citation statements)
references
References 28 publications
16
411
4
32
Order By: Relevance
“…2 Similarly, before transplantation, the presence of GERDinduced aspiration has been linked to pulmonary failure, particularly in patients with IPF. 3 Therefore, GERD is thought to play a significant role in the decline in lung function before transplantation and the rejection after lung transplantation, likely by causing aspiration-mediated lung injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Similarly, before transplantation, the presence of GERDinduced aspiration has been linked to pulmonary failure, particularly in patients with IPF. 3 Therefore, GERD is thought to play a significant role in the decline in lung function before transplantation and the rejection after lung transplantation, likely by causing aspiration-mediated lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…The following topics were discussed: (1) pathophysiology of GERD-induced pulmonary symptoms, (2) GERD evaluation before and after lung transplantation, (3) outcome of lung transplantation for IPF and scleroderma, and (4) role of laparoscopic fundoplication before or after lung transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly relevant since it has been shown in previous series that a large number of IPF patients lack of GERD symptoms despite objective evidence of GERD at endoscopy or reflux monitoring. [2][3][4] Indeed, in IPF patients a phenomenon so called "silent reflux" has been described and the consequent microaspiration into the lungs has been mainly implicated in the pathogenesis of this condition. 5 In contrast with the paper of Lee et al, 1 many previous studies have reported a higher prevalence of GERD in patients with IPF, [2][3][4] and this important relationship has been sustained by pathophysiological investigations which allowed to detect objectively the presence of an abnormal reflux.…”
Section: To the Editormentioning
confidence: 99%
“…[2][3][4] Indeed, in IPF patients a phenomenon so called "silent reflux" has been described and the consequent microaspiration into the lungs has been mainly implicated in the pathogenesis of this condition. 5 In contrast with the paper of Lee et al, 1 many previous studies have reported a higher prevalence of GERD in patients with IPF, [2][3][4] and this important relationship has been sustained by pathophysiological investigations which allowed to detect objectively the presence of an abnormal reflux. For instance, Lee et al 1 did not mention a study in IPF individuals performed with 24-hour impedance pH monitoring, which is nowadays considered to be the best test for measuring gastroesophageal reflux, also in case of atypical manifestations.…”
Section: To the Editormentioning
confidence: 99%
“…First, there is wide presentation of GER in IPF patients [4]. Second, age, smoking and male gender playing a role as a shearing risk factors in both IPF and GER [5].…”
Section: Introductionmentioning
confidence: 99%